DIGITAL TRANSFORMATION IN EDUCATION FINANCING: OPPORTUNITIES AND CHALLENGES IN THE ERA OF TECHNOLOGICAL DISRUPTIONS - Nikmatul Hikmah; Niken Lufi Anggini; Nur Anim Jauhariyah (ICO EDUSHA, 2024)
Digital transformation in the education sector has changed the education financing landscape by introducing innovative technologies such as blockchain, crowdfunding, and digital financial management systems. While offering great opportunities in increasing transparency, efficiency, and accessibility of financing, this transformation also presents challenges, including the digital divide, infrastructure limitations, and data security risks. This study focuses on the implementation of digitalization in education financing at the Yayasan Pondok Pesantren Darussalam Blokagung Banyuwangi, using a qualitative approach and case studies. The findings show that digitalization facilitates more efficient and transparent education financial management, opens access to alternative financing sources, and increases community participation through crowdfunding. However, data security and privacy challenges need to be addressed to ensure the success of this transformation. This study emphasizes the importance of collaboration between the government, educational institutions, and the private sector in optimizing the use of digital technology while minimizing its risks, thus creating an inclusive, efficient, and sustainable education financing system.